γ-Glutamyl-Transpeptidase-Resistant Glutathione Analog Attenuates Progression of Alzheimer's Disease-like Pathology and Neurodegeneration in a Mouse Model - Ye In Christopher Kwon; Wei Xie; Haizhou Zhu; Jiashu Xie; Keaton Shinn; Nicholas Juckel; Robert Vince; Swati S. More; Michael K. Lee (MDPI AG, 2021)
Oxidative stress in Alzheimer's disease (AD) is mediated, in part, by the loss of glutathione (GSH). Previous studies show that γ-glutamyl transpeptidase (GGT)-resistant GSH analog, Ψ-GSH, improves brain GSH levels, reduces oxidative stress markers in brains of APP/PS1 transgenic mice, a mouse model of AD, and attenuates early memory deficits in the APP/PS1 model. Herein, we examined whether Ψ-GSH can attenuate the disease progression when administered following the onset of AD-like pathology in vivo. Cohorts of APP/PS1 mice were administered Ψ-GSH for 2 months starting at 8 month or 12 months of age. We show that Ψ-GSH treatment reduces indices of oxidative stress in older mice by restoration of enzyme glyoxalase-1 (Glo-1) activity and reduces levels of insoluble Aβ. Quantitative neuropathological analyses show that Ψ-GSH treatment significantly reduces Aβ deposition and brain inflammation in APP/PS1 mice compared to vehicle-treated mice. More importantly, Ψ-GSH treatment attenuated the progressive loss of cortical TH+ afferents and the loss of TH+ neurons in the locus coeruleus (LC). Collectively, the results show that Ψ-GSH exhibits significant antioxidant activity in aged APP/PS1 mice and chronic Ψ-GSH treatment administered after the onset of AD pathology can reverse/slow further progression of AD-like pathology and neurodegeneration in vivo.